Su una lettura saussuriana - Paolini, Michele (Verbum – Analecta Neolatina, 2017)
The initial aim of this paper was to analyse, in the form of a brief informative book review, Massimo Prampolini’s work Ferdinand de Saussure (Roma, Carocci editore, 2017). This book aroused such a lively interest that it has prompted us to expand our original project. Current readings of Saussure’s work can be summarised as follows: an “early Saussure”, based on the publication of the Cours de linguistique générale (1916); a “second Saussure”, witnessed by his Écrits de linguistique générale (2002), documenting the research directed towards the philological study of the Swiss linguist’s manuscripts, and a “third Saussure”, “esoteric”, developed in the “theory of anagrams”, as can be seen in Saussure’s notes, for a long time unconsidered because unpublished, and unpublished because scientifically unsolved. The “second Saussure” offers the reader the most convincing multifaceted view of language which can be achieved today by reading Saussurean studies.